Comparing Cervical Vertebra Maturation and Modified Middle Phalange of Finger Maturation(MP3) for Assessment of Pubertal Growth Spurt - Hayat, Sumbal; Nasrullah Mengal; Hammal Baloch; Fakhira Nizam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the pubertal growth spurt by keeping Cervical Vertebra Maturation Index as standard and comparing modified middle phalange of 3rd finger maturation (MP3) stages with it. Study Design: Comparative cross- sectional study. Place and Duration of Study: Orthodontic Department, Sandeman Provincial Hospital, Quetta Pakistan, from Jan to Jun 2019. Methodology: One hundred and ten patients, aged 9 to 19 years with an evident appearance of bones on radiograph. First four cervical vertebrae with evident inferior border were included. Patients with previous history of bone disease and major illness, muscular dystrophy cases, congenital malformation of hand, cervical vertebrae, and wrist region cases and low quality X-ray with poor contrast were excluded. Results: Cervical Vertebra Maturation Index and modified middle phalange of 3rd finger maturation (MP3) were occurring earlier in the females (36 patients (33%) & (36 patients (33%) respectively in the comparison of males (13 patients (11%) & (13 patients (12%) respectively; moreover, there was the significant association between the Cervical Vertebra Maturation Index and modified middle phalange of 3rd finger maturation (MP3) stages as found by the chi-square test (p-value= <0.001). Conclusion: The significant association was found in the Cervical Vertebra Maturation Index stages and the MP3 stages. Females showed earlier signs of physiological maturity with same chronological age.